The Albania settlement of Griqualand West, 1866-1878 - Kurtz, June Margaret (Rhodes University, Faculty of Humanities, Department of History, 1988)
The history of the Albania Settlement of Griqualand West is examined from its beginnings in 1866 to its demise in 1878. Albania was very much a product of its time. Nineteenth century British colonial policy was basically expansionist, despite minor fluctuations caused by the various influences affecting it, such as the Free Trade and Mercantilist doctrines, social factors within Britain and events within the colonies themselves. From 1815 colonial settlements were fairly common in British territory, especially after Wakefield had provided a convincing theoretical framework for them. Within South Africa itself there are differing interpretations of what motivated British policy and of the role of the missionaries, while the changing political and economic landscape markedly affected Britain's decisions. British Government settlement schemes were undertaken mainly for social or military reasons, but there were also many settlements founded by land speculators. The economically depressed 1860s hit the Eastern Cape hard and this, combined with the transition to sheep farming, which created considerable land hunger, made the Albania scheme attractive to Eastern Cape farmers. The Griqua people led by Andries Waterboer had made a great effort to establish hegemony north of the Orange River, over the Sotho-Tswana and other Griqua chiefs. By 1866 the attempt had failed and Free State farmers were encroaching onto Nicholas Waterboer's lands. When Waterboer's agent, David Arnot, proposed the establishment of a settlement of Albany men to act as a "Wall of Flesh", Waterboer accepted the idea. Arnot's motivation was also land speculation in an area where diamonds were likely to push up land values. From its inception the settlement was dogged by quarrels, mainly over land, amongst the parties involved - the Griqua, brutally removed to make way for the settlers; the settlers, dissatisfied with the land tenure system and their administration; Arnot; the British and the encroaching Boer farmers . After the 1871 annexation of Griqualand West, into which Albania was absorbed, it took seven years, two Land Commissions, a Land Court and a special Land Claims Commissioner to sort out the tangled claims and bring order to the area and Albania's history to a close.
Keywords: Land settlement -- South Africa -- Cape of Good Hope; Albania (South Africa); Griqualand West (South Africa) -- History